1982
DOI: 10.1002/ijc.2910300413
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐tumor activity of daunorubicin linked to poly‐L‐aspartic acid

Abstract: Daunorubicin was bound to poly-L-aspartic acid via the methylketone side chain of the drug to avoid reaction of the sugar amino group believed to be essential for optimal drug activity. Attachment of the drug to the polyamino acid by an ester linkage was achieved by nucleophylic substitution reaction of 14-bromo-daunorubicin. Compared with free daunorubicin, the polymeric derivative was less cytotoxic to HeLa cells in vitro, but more effective against all tumor models tested (P388 leukemia, Gross leukemia, MS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1985
1985
2003
2003

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…The vesicant action of (Zunino et al, 1982(Zunino et al, , 1984 and, as already observed for other antitumour drugs, optimal treatment was at the maximum tolerated doses, in antitumour activity experiments the dose levels were usually selected in the range of the highest non-toxic doses (.LD1O). The relative effectiveness of doxorubicin, in the survival time than did doxorubicin.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The vesicant action of (Zunino et al, 1982(Zunino et al, , 1984 and, as already observed for other antitumour drugs, optimal treatment was at the maximum tolerated doses, in antitumour activity experiments the dose levels were usually selected in the range of the highest non-toxic doses (.LD1O). The relative effectiveness of doxorubicin, in the survival time than did doxorubicin.…”
Section: Resultsmentioning
confidence: 99%
“…Reduction of local toxicity is also consistent with the observation that high doses of the conjugate were well tolerated after i.p. administration (Zunino, 1982). Again, this might have clinical relevance because of the therapeutic potential of doxorubicin in the intraperitoneal chemotherapy of abdominal neoplastic diseases (Myers & Collins, 1983).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations